On-farm diversity assessment and evaluation of finger millet genotypes in the mid-hills of Nepal - Yadav, R.K.; Gurung, R.; Dhakal, R.; Gautam, S.; Adhikari, A.R.; Ghimire, K.H.; Sthapit, B.R. (Update Publishing House, 2018)
The objective of the study is to assess the phenotypic diversity among the finger millet genotypes and evaluate overall performance for the recommendation of genotypes to the farming community of mid hills of Nepal. The overall performance of 8 candidate genotypes selected from diversity block of 46 varieties in 2015, were assessed in randomized complete block design (RCBD) with three replicates under on-farm conditions in Lamjung district during 2016. Highly significant (p≤0.01) variability among the selected 8 genotypes for agro-morphological traits viz., plant height, number of fingers per head, grain yield, 1000 grain weight, straw yield, days to heading and maturity was revealed. Strong inter-correlation among grain yield, plant height, time to flowering and straw yield was detected. The traits viz., plant height, grain yield, straw yield, days to heading and days to maturity were the most important traits contributing to the overall variability and thus, provide options for selection.